PERANCANGAN SISTEM INFORMASI LPPM POLITEKNIK PIKSI GANESHA BERBASIS WEB MENGGUNAKAN VS CODE FRAMEWORK LARAVEL - Lazuar Shaputra, Rizky; Suwartika, Rini (POLITEKNIK PIKSI GANESHA, 2024)
LPPM at Politeknik Piksi Ganesha faces challenges with its manual system. This study designs a web- based system information using Laravel to enhance data management efficiency. Methods include needs analysis, design with use case and activity diagrams, implementation with PHP and Laravel, and Blackbox testing. Result show that the system improves information access and coordination.